The relationship between fear of missing out, social media flow experience and social media addiction among university students in Malaysia - Ng, Jing Wen; See, Rou Yee; Vooi, Hao Zheng (2024)
Social media have brought a lot of benefits to our life, however if abuse, it might lead to social media addiction. Due to this concern, the current study analyses the connection between Malaysian undergraduate students' Social Media Addiction (SMA), Social Media flow (SM flow), and Fear of Missing Out (FoMO). Three instruments which are ten-item Fear of Missing Out Scale, Brailovskaia’s Social Media flow scale and six-item Bergen Social Media Addiction Scale were used in the current study. In term of result design, quantitative cross-sectional research design was applied in the present study. Purposive sampling method was applied, participant must be a Malaysian undergraduate student, aged 18 or above, currently residing in Malaysia. A total number of 227 participants (M: 20.83, SD: 1.61), wherein most of them are UTAR students (95.5%). All the data was obtaining online self-report survey. All the hypothesis in the present study were supported, result indicated a significant positive relationship existed between FoMO and SMA, between SM flow and SMA, and between FoMO and SM flow, while SM flow play a mediating role between FoMO and SMA. These results were consistent was consistent with previous study conducted by Brailovskaia and Margraf (2023). In sum, current research on Fear of Missing Out (FoMO), flow experience of social media, and addictive behavior to social media in Malaysian university students offers insights for interventions promoting digital well-being. FoMO drives social media flow, contributing to addiction. Flow Theory helps understand this relationship, crucial especially amidst COVID-19 stress, highlighting the importance of targeted interventions.